SCALING UP HUMANITARIAN AGENDA WITHIN COMMUNAL VIOLENCE IN MYANMAR - Lestari, Mega Ayu (UI Scholars Hub, 2018)
Following the historical origins, social triggers, and ethics about their status of citizenship, theRohingya should be treated properly as human-being. Even there are contradictions between the Burma Citizenship Law who did not admit them as an ethnic group of Myanmar, and Rohingya leaders who claimed as the descendants of the precolonial Muslim community of Rakhine State, it could not allow discrimination, confiscation of land, violence, and any other forms of injustice against the Rohingya. Hence, this paper would like to explain how they can be recognized in achieving their rights and reshaping the importance of humanitarian agenda, in which these are able to address the on-going abuse and exploitation within them and the needs of both critical agents and strong political solutions to alleviate the suffering of Rohingya. It also might be considered as an effort to broaden perspective among society in the meaning of refugees‟ law and protection. In case of promoting humanitarian agenda of the Rohingya, the paper has underscored this steps: 1) understanding the root cause of the stateless of Rohingya, 2) redefining values of solidarity; especially in ASEAN countries, 3) identifying the best feasible humanitarian action and initiatives, 4) reframing media and communication strategy to help encourage public opinion; and ultimately public policy to end the crisis of Rohingya. Through science-policy interface, it provides networking schemes and humanitarian programs designed to activate their voices and initiatives, to invest for capacity- building and creating local leaders within Rohingya community. This paper can contribute to build a greater accountability at national and international level while measuring the impact of multisectoral partnerships that use an interdisciplinary approach. As a result, it will affect on the Rohingya recognition, and close their gaps and needs as a move towards well-being community.